Anthurium guaratinguense (Araceae), a new species with cordate leaves from Bahia Atlantic Forest, Brazil - Valadares, Rodrigo Theófilo; Magno, Alexandre; Medeiros, João Paulo S. (Phytotaxa, 2026)
A new species of Anthurium sect. Urospadix (Araceae) from southeastern Brazil is described and illustrated. Anthurium guaratinguense was first recognised in cultivation and later confirmed in its natural habitat. Vegetatively, the species has a much thicker stem than its congeners. The peduncle of the new species is also much smaller, but the main reproductive characteristic is the presence of a bright light green spadix until the end of anthesis. Morphological affinities with related taxa are discussed, and notes on its ecology, distribution and conservation status are provided.